Screening of Chemical Composition of Crude Water Extract of Different Cassava Varieties (2013)
Chemical composition of three sources of crude cassava water extract (CCWE) was evaluated in different varieties of cassava (MS6 Manihot Selection (local variety), TMS 30555 Tropical Manihot Selection (Improved variety) and Bulk (crude cassava water front cassava processing site). Crude cassava water extract front the pulp of cassava fresh roots was prepared and the Chemical composition was determined in the analytical laboratory. The result of the analysis showed that, hydrocyanic acid (HCN) and with elements such as Calcium (Ca), Sodium (Na). Magnesium (Mg). Manganese (Mn), Iron (Fe), Sulphur (S), Copper (Cu) and Zinc (Zn). Nitrogen (N), Phosphorous (P) and Potassium (K) were found in the extract. The study showed that due to the presence of hydrocyanic acid in the extract, this waste found around the cassava Processing sites possesses phytotoxic effects on weeds/vegetation in form of leaf discoloration (yellowing), wilting and eventually death. Crude cassava water extract showed a probable natural herbicide which can be used by the peasant farmers because it is environmental friendly and easily biodegradable into harmless compounds in the environment